If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2r + -16 = -6 + 4r Reorder the terms: -16 + 2r = -6 + 4r Solving -16 + 2r = -6 + 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. -16 + 2r + -4r = -6 + 4r + -4r Combine like terms: 2r + -4r = -2r -16 + -2r = -6 + 4r + -4r Combine like terms: 4r + -4r = 0 -16 + -2r = -6 + 0 -16 + -2r = -6 Add '16' to each side of the equation. -16 + 16 + -2r = -6 + 16 Combine like terms: -16 + 16 = 0 0 + -2r = -6 + 16 -2r = -6 + 16 Combine like terms: -6 + 16 = 10 -2r = 10 Divide each side by '-2'. r = -5 Simplifying r = -5
| 4g+20=10g+5 | | Y=8sec(5x) | | 2(x-7)-9=-23 | | 5(3x+2)=7 | | 3n+2=1n+12 | | (x+10)(x+5)+(x+-3)(x+12)+(x+11)(x+30)=106 | | 2x^4=35 | | 1n+9=4n+3 | | -16x^2+240x+20=0 | | 2.5x+2.4=7.8 | | 4m-8+2m=2(3m-4) | | 3x^2-3=2x-1 | | 3n+6=4n+1 | | 5-21=2a | | solvex+0.08(60)=0.20(60+x) | | 3(x+5)=x+3+2x | | Sen(2x)+sen(4x)=0 | | 47.1=29.7-0.2x | | -47(x-11)-34=10-12 | | 2m-28=9m | | 2-7k=-4(k+1)-3 | | 4(x-8)=2x+6-x | | 3z-19=123 | | 2[t-(2t+8)+6]=2(t+2) | | 5x(x+8)+5x(6-x)=9(12+x)-8(7-x) | | 7(-6)(5)= | | 4z^2+3z-1=0 | | 2x^2-3y=32 | | -(z+7)+(5z+1)=5(z+1) | | 5x-19=3x+6 | | 3x(x+3)=24 | | 27x=33 |